Titanium white waste acid resource utilization treatment process
Patent Information
- Application Number
- CN202611165336.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
然而,现有吸附材料在强酸性条件下稳定性不足、选择性差、难以实现多种污染物协同去除及有价资源同步回收,且制备工艺复杂、成本较高,限制了其在钛白废酸处理中的大规模应用
(1)本发明通过精确控制预调质阶段的pH值,利用三价铁与二价铁溶度积的差异,实现了三价铁的选择性沉淀分离,而二价铁则保留在上清液中进入后续工序。更为关键的是,本发明所采用的巯基和氨基双功能化铈钐共掺杂铁氧体-二氧化硅复合多孔微球,其表面的巯基官能团对二价铁离子具有高效的配位捕获能力,能够将废酸中的铁离子富集于材料表面。经稀盐酸洗脱再生后,所得洗脱液中含有高浓度的二价铁离子,可作为铁盐产品直接用于水处理或进一步加工为铁系颜料。同时,在一级沉淀池中分离得到的氢氧化铁沉淀,经洗涤干燥后可作为炼铁原料,直接进入钢铁冶金流程。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of resource utilization technology, specifically relating to a process for the resource utilization and treatment of waste acid from titanium dioxide. Background Technology
[0002] The sulfuric acid process is the mainstream technology for titanium dioxide production globally, but it generates a large amount of waste sulfuric acid during production. This waste acid contains a high concentration of sulfuric acid, as well as significant amounts of ferrous sulfate, magnesium sulfate, aluminum sulfate, and trace amounts of valuable metals such as scandium, vanadium, and titanium. Direct discharge of this waste acid would not only cause severe environmental pollution and ecological damage but also lead to the waste of substantial sulfuric acid resources and valuable metals. From the perspective of metal production and resource extraction, the iron, scandium, and titanium contained in titanium dioxide waste acid have extremely high recycling value. Efficient extraction would significantly reduce raw material costs for metal production and decrease reliance on primary mineral resources. With increasingly stringent national standards for industrial waste emissions and the promotion of circular economy policies, the harmless treatment and resource utilization of titanium dioxide waste acid has become a critical technical challenge that the titanium dioxide industry urgently needs to address.
[0003] Currently, domestic and international technologies for treating waste acid from titanium dioxide mainly include concentration and recovery, neutralization precipitation, diffusion dialysis, solvent extraction, and membrane electrolysis. Concentration and recovery increases sulfuric acid concentration through heating and evaporation, but it is energy-intensive and prone to scaling and clogging. Neutralization precipitation, while simple to operate, consumes large amounts of alkaline substances, generating large quantities of difficult-to-dispose-of titanium gypsum solid waste, which contains impurities such as iron and aluminum, resulting in low-quality gypsum and hindering high-value utilization. Diffusion dialysis can separate sulfuric acid from metal ions, but the recovered sulfuric acid concentration is limited, and membrane materials are expensive. Solvent extraction can selectively recover valuable metals, but the process is complex, requires large amounts of organic solvents, and poses a risk of secondary pollution. Membrane electrolysis combined with selective electrodialysis can achieve efficient recovery of sulfuric acid and iron, but it involves large equipment investment and high energy consumption. In recent years, research on using adsorption materials to treat industrial waste acid has received widespread attention. Layered bimetallic hydroxides, spinel ferrites, and other inorganic materials have shown potential application prospects due to their high specific surface area and good chemical stability. However, existing adsorbent materials suffer from insufficient stability and poor selectivity under strong acidic conditions, making it difficult to achieve synergistic removal of multiple pollutants and simultaneous recovery of valuable resources. Furthermore, their preparation processes are complex and costly, limiting their large-scale application in the treatment of titanium dioxide waste acid. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a process for the resource utilization and treatment of waste acid from titanium dioxide production.
[0005] In a first aspect, the present invention provides a process for the resource utilization and treatment of waste acid from titanium dioxide production, comprising the following steps: S1. By weight, 95-105 parts of titanium dioxide waste acid, after sedimentation and coarse filtration, are pumped into a reaction tank. 0.1-0.5 parts of calcium sulfate dihydrate are added beforehand. The mixture is stirred at room temperature, and a suspension containing 15-25 parts of calcium oxide and 135-225 parts of deionized water is added. The pH is adjusted to 3.2-3.5, and the mixture is stirred continuously and allowed to settle to obtain a supernatant and a lower precipitate. The lower precipitate is then dehydrated by pressure filtration to obtain a mother liquor. S2. Pump the supernatant obtained in step S1 into an adsorption tower filled with 5-8 parts of thiol and amino bifunctional cerium samarium co-doped ferrite-silica composite porous microspheres. Apply an electromagnetic field to the outer wall of the adsorption tower and collect the adsorbed wastewater. The adsorption tower is filled with saturated material. S3. Discharge the saturated material into a magnetic separation tank. Place a permanent magnet at the bottom of the magnetic separation tank to obtain the separated supernatant and the magnetically enriched material. Return the separated supernatant to the reaction tank in step S1. Wash the magnetically enriched material with deionized water, transfer it to a regeneration reaction tank, add 15-25 parts of dilute hydrochloric acid solution with pH=2.0-2.5, stir, and separate again by magnetic field to obtain the regenerated mercapto- and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres and desorption regeneration solution. Wash the regenerated mercapto- and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres with deionized water, vacuum dry them at 58-62℃, and then recycle them. S4. Combine the desorption regeneration liquid obtained in step S3 with the filter press mother liquor obtained in step S1 and pump them into the oxidation reaction tank. Adjust the pH to 3-4, add 0.5-1.0 parts of hydrogen peroxide, and introduce air to obtain the oxidized feed liquid. Pump the oxidized feed liquid into the primary sedimentation tank, adjust the pH to 4.0-5.0, let it settle, and separate to obtain the precipitate and the separated supernatant. Transfer the separated supernatant to the secondary sedimentation tank, adjust the pH to 7.5-8.5, stir continuously, let it settle, and separate to obtain the upper supernatant and the lower precipitate. Discharge the upper supernatant. Filter the lower precipitate and dry it to obtain calcium sulfate dihydrate. Pump the adsorbed wastewater obtained in step S2 into the neutralization tank, add lime milk to adjust the pH to 6-9, and let it settle.
[0006] In this invention, the process mechanism for the resource utilization of titanium dioxide waste acid is a multiphase equilibrium-driven chemical transformation process involving acid-base neutralization, induced crystallization, synergistic adsorption, and selective oxidation. At the initial stage of the process, the sulfuric acid concentration in the waste acid is extremely high. By pre-adding calcium sulfate dihydrate seed crystals, a kinetic advantage for heterogeneous nucleation can be established in the system, effectively avoiding the explosive disordered nucleation during precipitation. This allows the calcium sulfate produced by the subsequent addition of lime slurry to grow directionally, forming large-particle crystals that are easy to filter and dehydrate. By precisely adjusting the pH of the system and utilizing the differences in the hydrolysis equilibrium constants of different metal ions, ferric iron first reaches its solubility product and precipitates, while ferrous iron is temporarily retained in the liquid phase, achieving preliminary phase separation of impurity elements. In the core adsorption stage, thiol- and amino-functionalized cerium-smarium co-doped ferrite-silica composite porous microspheres form a stable fluidized state in the adsorption tower under the assistance of an alternating electromagnetic field, greatly eliminating liquid-solid mass transfer resistance. At this point, the thiol functional groups on the surface of the thiol- and amino-bifunctionalized cerium-sammarium co-doped ferrite-silica composite porous microspheres utilize their high electron cloud density to form stable chelate rings with ferrous iron, aluminum, and other cations in the waste acid. Simultaneously, the amino groups spontaneously combine with hydrogen ions in the acidic wastewater to achieve protonation. The resulting positive charge centers strongly attract sulfate anions through strong Coulomb forces, while the doped rare earth ions form surface complexes with oxygen atoms in the sulfate ions through their empty electron orbitals. This multi-effect synergistic mechanism significantly enhances the purification depth of the waste acid. During the regeneration stage of the thiol- and amino-bifunctionalized cerium-sammarium co-doped ferrite-silica composite porous microspheres, rinsing with a very low concentration of dilute hydrochloric acid solution, through the competitive occupation of active sites by a high concentration of hydrogen ions, forces the desorbed components into the regeneration solution. In the final oxidation precipitation process, hydrogen peroxide, as a cleaning oxidant, combined with air aeration, utilizes the generated active free radicals to rapidly convert the residual divalent iron into trivalent iron. Subsequently, through two-stage pH control, low-grade iron raw materials and high-purity gypsum products are processed separately, achieving a closed-loop treatment of waste acid from titanium dioxide production by reducing its volume and recycling it for resource recovery.
[0007] According to a preferred embodiment of the present invention, in step S1, the settling time is 1-2 hours.
[0008] According to a preferred embodiment of the present invention, in step S2, the filling volume of the thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres is 60-70% of the effective volume of the adsorption tower.
[0009] According to a preferred embodiment of the present invention, in step S3, the magnetic field strength of the permanent magnet is 0.2-0.3T.
[0010] According to a preferred embodiment of the present invention, in step S4, the drying temperature is 105-120°C.
[0011] According to a preferred embodiment of the present invention, the preparation steps of the thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres include: A1. By weight, dissolve 0.8-1.2 parts of cerium chloride hexahydrate, 0.4-0.6 parts of samarium chloride hexahydrate, 5.1-5.5 parts of ferric chloride hexahydrate, and 3.1-3.4 parts of ferrous sulfate heptahydrate in a mixed solvent consisting of 80-100 parts of deionized water and 25-30 parts of anhydrous ethanol. Under nitrogen protection, stir and ultrasonically disperse. At 4-6℃, add dropwise a mixed solution containing 10-12 parts of sodium hydroxide, 1.5-2.0 parts of anhydrous sodium carbonate, and 120-140 parts of deionized water. After the addition is complete, ripen under nitrogen protection to obtain the precursor. A2. Vacuum filter the precursor to obtain precipitate A; wash precipitate A with deionized water, transfer it to a reaction vessel, add 5-10 parts of trisodium citrate aqueous solution, replenish with deionized water, adjust the pH to 9.5-10.0, and hydrothermally crystallize at 178-182℃; after the reaction is complete, allow it to cool naturally, centrifuge to obtain precipitate B; wash precipitate B with deionized water and anhydrous ethanol, and vacuum dry at 58-62℃ to obtain nanocrystalline nuclei; A3. 5.0 parts of nanocrystalline nuclei were ultrasonically dispersed in a mixed solvent consisting of 30-40 parts of deionized water and 120-140 parts of anhydrous ethanol. 1.4-1.6 parts of hexadecyltrimethylammonium bromide and 1.8-2.2 parts of tetraethyl orthosilicate were added, and the pH was adjusted to 9.0-9.5. The mixture was stirred at 38-42℃. Magnetic separation was performed to obtain product A. After drying, product A was dispersed in 150-200 parts of anhydrous ethanol solution containing 5-8 parts of ammonium nitrate. Extraction was performed with stirring at 58-62℃, followed by magnetic separation to obtain product B. Product B was placed in a tube furnace and calcined at 400-450℃ under a nitrogen atmosphere. After cooling, the calcined product was obtained. The calcined product was placed in deionized water and treated at 80-90℃. After centrifugation, solid A was obtained. Solid A was washed with deionized water and vacuum dried at 98-102℃ to obtain composite microspheres with a mesoporous silica shell. A4. Disperse 3.0 parts of composite microspheres with mesoporous silica shells in 85-95 parts of anhydrous toluene, add 0.7-0.9 parts of 3-mercaptopropyltrimethoxysilane and 0.3-0.5 parts of 3-aminopropyltriethoxysilane and mix. Under nitrogen protection, reflux at 108-112℃. After the reaction is completed, magnetic separation is performed to obtain solid B. Solid B is washed with anhydrous toluene and anhydrous ethanol and dried under vacuum at 60-80℃.
[0012] In this invention, the preparation mechanism of the thiol- and amino-functionalized cerium-sammarium co-doped ferrite-silica composite porous microspheres embodies a deep integration of interfacial chemical modification and nano-confinement effects. First, in a reducing atmosphere under nitrogen protection, cerium chloride hexahydrate, samarium chloride hexahydrate, and divalent and trivalent ferric salts are dispersed at the molecular level in a mixed medium of water and ethanol. When an alkaline precipitant is slowly added dropwise, cations undergo instantaneous nucleation reactions with hydroxide and carbonate ions to generate precursor colloids. In the subsequent high-temperature hydrothermal environment, citrate ions act as complexing stabilizers, guiding cerium and samarium ions into the spinel lattice of the ferrite. This insertion of heteroatoms induces microscopic distortion of the lattice, significantly enhancing the superparamagnetic response of the microspheres and providing them with unique redox catalytic centers. Next, using oriented micelles formed by the surfactant hexadecyltrimethylammonium bromide in the liquid phase as a soft template, tetraethyl orthosilicate underwent hydrolysis and condensation in a weakly alkaline environment. Through dehydration reactions between silanol groups, a highly ordered mesoporous silica shell was constructed on the surface of the magnetic core. Subsequent high-temperature calcination completely oxidized and decomposed the organic template molecules, leaving numerous open nanoscale channels in the shell. To repair the deactivation of surface active sites caused by calcination, the material was hydrothermally activated in near-boiling deionized water, causing the surface siloxane chains to reopen and transform into highly active hydroxyl groups. In the final functionalization stage, 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane underwent a condensation reaction in anhydrous toluene solvent, successfully anchoring the highly coordinating thiol groups and electrostatically responsive amino groups onto the pore wall surface, constructing a multifunctional composite material with both chemical chelation and physical attraction sites.
[0013] According to a preferred embodiment of the present invention, in step A1, the ultrasonic dispersion time is 20-40 min.
[0014] According to a preferred embodiment of the present invention, in step A2, the hydrothermal crystallization time at 178-182°C is 24-30 hours.
[0015] According to a preferred embodiment of the present invention, in step A3, the calcination time at 400-450°C is 2-4 hours.
[0016] According to a preferred embodiment of the present invention, in step A4, the reflux reaction at 108-112°C is carried out for 12-14 hours.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves selective precipitation and separation of ferric iron (Fe3+) by precisely controlling the pH value during the preconditioning stage and utilizing the difference in solubility products between ferric and ferrous iron (Fe2+), while ferrous iron (Fe2+) remains in the supernatant for subsequent processes. More importantly, the thiol- and amino-functionalized cerium-sammarium co-doped ferrite-silica composite porous microspheres used in this invention have a highly efficient coordination and capture ability for ferrous ions on their surface due to their thiol functional groups, which can enrich the iron ions in waste acid on the material surface. After elution and regeneration with dilute hydrochloric acid, the resulting eluent contains a high concentration of ferrous ions and can be used directly as an iron salt product for water treatment or further processed into iron-based pigments. At the same time, the ferric hydroxide precipitate separated in the primary sedimentation tank can be used as a raw material for ironmaking and directly enter the iron and steel metallurgical process after washing and drying.
[0018] (2) From the overall process flow perspective, this invention takes titanium dioxide waste acid as the treatment object and achieves efficient separation and recovery of valuable components in the waste acid through four steps: lime slurry neutralization and preconditioning, magnetically stabilized fluidized bed dynamic adsorption, dilute hydrochloric acid regeneration, and two-stage precipitation recovery. In step S1, calcium sulfate dihydrate seed crystals are added in advance and the lime slurry addition rate is controlled to make the precipitate particles large and easy to filter, solving the industry problem of large amounts of difficult-to-treat titanium gypsum generated by the traditional lime neutralization method. In step S2, a magnetically stabilized fluidized bed adsorption tower is used. The magnetic composite microspheres are in a fluidized state under the action of an alternating electromagnetic field, which fully contacts the waste acid and has high mass transfer efficiency, making it suitable for treating industrial wastewater. The material after adsorption saturation can be quickly separated by an external magnetic field, eliminating high-energy-consuming operations such as centrifugation or filtration, and significantly simplifying the solid-liquid separation process. In step S3, a dilute hydrochloric acid solution with strictly controlled pH is used for elution and regeneration, making the material recyclable and reducing operating costs.
[0019] (3) The thiol and amino bifunctionalized cerium-smarium co-doped ferrite-silica composite porous microspheres developed in this invention use cerium-smarium co-doped ferrite as the magnetic core, exhibiting superparamagnetic properties. The mesoporous silica shell is structurally stable after high-temperature calcination in a nitrogen atmosphere, protecting the internal magnetic core from corrosion by acidic solutions. The surface activation of the material abandons the traditional acid washing method and instead uses hot water heating hydrolysis treatment, which restores the density of surface silanol groups while avoiding the dissolution of the magnetic core, ensuring the stability of the material in multiple adsorption-regeneration cycles. In step S4, hydrogen peroxide and air are used for synergistic oxidation, rapidly oxidizing residual divalent iron to trivalent iron under acidic conditions, with high oxidation efficiency and no introduction of new impurities. Finally, this process recovers iron metal and sulfur resources from titanium dioxide waste acid, realizing the resource utilization of waste acid, and achieving both environmental and economic benefits. Detailed Implementation
[0020] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention. Example
[0021] This embodiment provides a process for the resource utilization and treatment of waste acid from titanium dioxide production, including the following steps: S1: Take 100g of titanium dioxide waste acid, remove large suspended particles by gravity sedimentation, then coarsely filter through a 200-mesh stainless steel screen, and pump the filtrate into the reaction vessel. Add 0.3g of calcium sulfate dihydrate as seed crystals beforehand, and stir at 200rpm at room temperature. Prepare lime milk suspension: Mix 20g of calcium oxide with 180g of deionized water and stir to prepare a 10wt% suspension. Slowly add the lime milk suspension at a rate of 0.5BV / h under stirring conditions, while monitoring with an online pH meter, until the system pH rises to 3.35. Continue stirring at 200rpm for 30min to allow Fe... 3+ It fully precipitates as Fe(OH)3, while Fe 2+ Retain in solution. Stop stirring and let stand for 1.5 hours to settle, obtaining supernatant and lower precipitate. Dehydrate the lower precipitate (mainly a mixture of calcium sulfate dihydrate and Fe(OH)3) using a plate and frame filter press to obtain filter cake mother liquor, which is then used for other purposes.
[0022] S2: The supernatant obtained from S1 was continuously pumped into a magnetically stabilized fluidized bed adsorption tower at a space velocity of 2.0 BV / h. The adsorption tower had a height-to-diameter ratio of 5:1 and was filled with 6.5 g of thiol- and amino-bifunctionalized cerium-smarium co-doped ferrite-silica composite porous microspheres, with a filling volume of 65% of the effective volume of the adsorption tower. An alternating electromagnetic field with a frequency of 55 Hz and an intensity of 15 mT was applied to the outer wall of the tower to induce a magnetically stabilized fluidized state in the microspheres. Waste acid entered from the bottom of the tower and flowed out from the top, with a residence time of approximately 37.5 min. During the adsorption process, the thiol groups on the surface of the microspheres coordinated and captured Fe. 2+ Silyl hydroxyl groups capture Al 3+ Protonated -NH3 + and Ce 3 + / Sm 3+ Coordination sites synergistically adsorb SO4 2- Continue operation until the total iron concentration in the effluent is >50 mg / L or SO42- >50 mg / L. 2- Stop feeding when the concentration is >500 mg / L. Collect the adsorbed wastewater, and obtain saturated material in the adsorption tower.
[0023] S3: Discharge the saturated material into a magnetic separation tank. A 0.25T permanent magnet is placed at the bottom of the tank. Let it stand for 5 minutes to allow the microspheres to accumulate at the bottom. Separate the supernatant and the magnetically enriched material. The supernatant is returned to the reaction tank in S1 and combined with a new batch of waste acid for treatment. The magnetically enriched material is rinsed three times with 25g of deionized water and transferred to a regeneration reaction tank. Add 20g of a dilute hydrochloric acid solution (pH=2.3, prepared by diluting 37% concentrated hydrochloric acid) and stir at 300rpm for 30 minutes to allow the adsorbed metal ions and SO42- to react. 2- Desorption. The microspheres were separated again by magnetic field through a bottom permanent magnet (0.25T) to obtain regenerated microspheres and desorption regeneration solution. The regenerated microspheres were repeatedly washed with 12g of deionized water until the pH of the washing solution was >3.5, and then placed in a vacuum drying oven and dried at 60℃ and a vacuum degree of -0.09MPa for 8h to obtain recyclable microspheres.
[0024] S4: Combine the desorption regeneration solution obtained in step S3 with the filter press mother liquor generated in step S1, and pump the mixture into an oxidation reactor. Adjust the pH of the combined solution to 3.5 using 1.0 mol / L dilute sulfuric acid or 10 wt% lime slurry, add 0.75 g of 30 wt% hydrogen peroxide, and simultaneously purge air at a rate of 0.75 m³ / (m²·min). Oxidize at room temperature for 30 min to remove residual Fe. 2+ Completely oxidized to Fe 3+ The oxidized liquid was obtained. The oxidized liquid was pumped into a primary sedimentation tank, and 10wt% lime slurry suspension was slowly added to adjust the pH to 4.5. After settling for 1 hour, Fe(OH)3 precipitate and supernatant were separated. The supernatant was transferred to a secondary sedimentation tank, and 10wt% lime slurry suspension was added to adjust the pH to 8.0. The mixture was stirred continuously at 120 rpm for 45 minutes and allowed to settle for 2 hours, separating the upper supernatant and lower precipitate. The upper supernatant was discharged after passing testing. The lower precipitate was filtered using a plate and frame filter press, and the filter cake was dried in an oven at 112℃ for 2 hours to obtain calcium sulfate dihydrate. The adsorbed wastewater obtained in step S2 was pumped into a neutralization tank, and 10wt% lime slurry was added to adjust the pH to 7.5. After settling, the supernatant was discharged after meeting standards, and the bottom sludge was filtered and combined with the lower precipitate from step S1 for disposal.
[0025] Preparation of thiol- and amino-bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres: A1: Dissolve 1.0 g cerium chloride hexahydrate, 0.5 g samarium chloride hexahydrate, 5.3 g ferric chloride hexahydrate, and 3.25 g ferrous sulfate heptahydrate in a mixed solvent consisting of 90 g deionized water and 27.5 g anhydrous ethanol. Transfer the solution to a three-necked flask, purge with nitrogen (flow rate 0.5 L / min) to remove air, and stir mechanically at 400 rpm for 30 min. Then, ultrasonically disperse the solution in an ultrasonic cleaner for 30 min (power 200 W, frequency 40 kHz) to form a homogeneous orange-red solution. Maintain the solution temperature at 5°C in an ice-water bath and continue vigorous stirring at 800 rpm under nitrogen protection. Prepare an alkaline precipitant: Dissolve 11 g sodium hydroxide and 1.75 g anhydrous sodium carbonate in 130 g deionized water to prepare a mixed alkaline solution. Add this alkaline solution dropwise to the above metal salt solution at a rate of 2.5 mL / min, maintaining the system temperature at 5°C during the addition. After the addition was completed, the mixture was stirred and matured at 600 rpm for 2 hours under nitrogen protection to form a gray-green gel-like precursor.
[0026] A2: The precursor obtained in A1 was vacuum filtered (vacuum degree -0.08 MPa, filter paper pore size 0.45 μm) to obtain precipitate A. Precipitate A was washed five times with 250 g of deionized water, filtered after each wash, until the pH of the washing solution reached 7.0. The washed precipitate was transferred to a 500 mL stainless steel high-pressure reactor lined with polytetrafluoroethylene (PTFE). 7.5 g of a 0.1 mol / L trisodium citrate aqueous solution was added, and deionized water was added to 80% of the reactor volume (approximately 400 mL). The pH of the system was adjusted to 9.75 with 1.0 mol / L NaOH solution, and the reactor was sealed. The reactor was placed in a temperature-controlled oven and heated to 180 °C at a heating rate of 2 °C / min. Hydrothermal crystallization was performed at this temperature for 27 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The reaction mixture was transferred to centrifuge tubes and centrifuged at 8000 rpm for 10 min. The supernatant was discarded to obtain black precipitate B. Precipitate B was washed three times alternately with 100g of deionized water and 25g of anhydrous ethanol (centrifuged after each wash), and then dried in a vacuum drying oven at 60℃ for 12h to obtain Ce / Sm co-doped magnetic ferrite nanocrystals.
[0027] A3: Take 5.0 g of Ce / Sm co-doped magnetic ferrite nanocrystals obtained in A2 and ultrasonically disperse them (200 W, 40 kHz, 20 min) in a mixed solvent consisting of 35 g of deionized water and 130 g of anhydrous ethanol to form a stable black suspension. Add 1.5 g of cetyltrimethylammonium bromide (CTAB) as a template agent and 2.0 g of tetraethyl orthosilicate (TEOS) as a silicon source to the suspension. Stir at 300 rpm for 30 min at room temperature to fully disperse CTAB and TEOS. Slowly adjust the pH of the suspension to 9.25 with ammonia (25 wt%) to trigger the sol-gel hydrolysis and condensation reaction of TEOS. Transfer the suspension to a 40 °C water bath and stir continuously at 350 rpm for 8 h to allow the silica precursor to be uniformly deposited on the surface of the nanocrystals. After the reaction is complete, use an external magnet (magnetic field strength 0.5 T) to magnetically separate the coated product from the system, discard the supernatant, and obtain product A. Product A was dried in a vacuum drying oven at 60℃ for 6 hours. The dried product A was dispersed in 175g of anhydrous ethanol solution containing 6.5g of ammonium nitrate, and extracted in a 60℃ water bath with stirring at 400rpm for 2 hours to remove the CTAB template agent. After extraction, the product was magnetically separated again using an external magnet (0.5T), and washed three times with 50g of anhydrous ethanol to obtain product B. Product B was placed in a tube furnace, and high-purity nitrogen gas (flow rate 0.3L / min) was introduced. The product was heated to 425℃ at a heating rate of 5℃ / min and calcined under a nitrogen atmosphere for 3 hours, then naturally cooled to room temperature to obtain the calcined product. The calcined product was transferred to a beaker, 200g of deionized water was added, and the mixture was heated to 85℃ and kept at a constant temperature for 45 minutes with stirring at 200rpm. After treatment, the product was centrifuged at 8000rpm for 10 minutes, and the supernatant was discarded to obtain solid A. Solid A was washed three times with 100g of deionized water (centrifuged after each wash) until the pH of the washing solution reached 6.8. Finally, it was dried in a vacuum drying oven at 100℃ for 4 hours to obtain composite microspheres with a mesoporous silica shell.
[0028] A4: Take 3.0 g of the composite microspheres obtained in A3, and ultrasonically disperse them (200 W, 40 kHz, 15 min) in 90 g of anhydrous toluene, then transfer the dispersion to a 250 mL three-necked flask. Add 0.8 g of 3-mercaptopropyltrimethoxysilane (MPTMS) and 0.4 g of 3-aminopropyltriethoxysilane (APTES) directly to the dispersion, purge with nitrogen (flow rate 0.2 L / min) to remove air, and heat to 110 °C under magnetic stirring for 12 h under reflux. After the reaction is complete, allow to cool naturally to room temperature, and magnetically separate using an external magnet (0.5 T). Discard the reaction solution to obtain solid B. Wash solid B twice with 50 g of anhydrous toluene and three times with 50 g of anhydrous ethanol, magnetically separating after each wash. Finally, solid B was placed in a vacuum drying oven and dried at 70°C and a vacuum of -0.09 MPa for 8 hours to obtain the final product: thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres. Example
[0029] The difference between this embodiment and Embodiment 1 is that this embodiment provides a process for the resource utilization and treatment of titanium dioxide waste acid, including the following steps: S1: Take 95g of titanium dioxide waste acid, and after sedimentation and coarse filtration, pump it into the reaction tank. Add 0.1g of calcium sulfate dihydrate in advance, stir at room temperature, add a suspension containing 15g of calcium oxide and 135g of deionized water, adjust the pH to 3.2, stir continuously for 30min, let it stand for 1h to obtain the supernatant and the lower precipitate; filter the lower precipitate to dehydrate and obtain the filter mother liquor.
[0030] S2: Pump the supernatant obtained in step S1 into an adsorption tower filled with 5g of thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres. Apply an electromagnetic field (frequency 50Hz, intensity 10mT) to the outer wall of the adsorption tower, collect the adsorbed wastewater, and obtain the adsorbed saturated material in the adsorption tower.
[0031] S3: Discharge the adsorbed saturated material into a magnetic separation tank. Place a 0.2T permanent magnet at the bottom of the magnetic separation tank to obtain the separated supernatant and the magnetically enriched material. Return the separated supernatant to the reaction tank in step S1. Wash the magnetically enriched material with 20g of deionized water, transfer it to a regeneration reaction tank, add 15g of dilute hydrochloric acid solution with pH=2.0, stir for 30min, and separate it again through a magnetic field to obtain the regenerated microspheres and desorption regeneration liquid. Wash the regenerated microspheres with 10g of deionized water, dry them under vacuum at 58℃, and then recycle them.
[0032] S4: Combine the desorption regeneration solution obtained in step S3 with the filter press mother liquor obtained in step S1 and pump them into an oxidation reaction tank. Adjust the pH to 3, add 0.5 g of hydrogen peroxide (30 wt%), and introduce air (0.5 m³ / (m²·min)) to obtain the oxidized feed solution. Pump the oxidized feed solution into a primary sedimentation tank, adjust the pH to 4.0 with 10 wt% lime slurry, let it stand for 1 hour to separate the precipitate and the supernatant. Transfer the supernatant to a secondary sedimentation tank. In the sedimentation tank, the pH was adjusted to 7.5 with 10wt% lime milk, stirred continuously for 45 minutes, and allowed to settle for 2 hours to separate the upper supernatant and the lower precipitate. The upper supernatant was discharged. The lower precipitate was filtered and dried at 105℃ to obtain calcium sulfate dihydrate. The adsorbed wastewater obtained in step S2 was pumped into the neutralization tank, 10wt% lime milk was added to adjust the pH to 6.5, and allowed to settle. The supernatant was discharged after meeting the standards. The bottom sludge was filtered and combined with the lower precipitate from step S1 for disposal.
[0033] Preparation of thiol- and amino-bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres: A1: Dissolve 0.8g cerium chloride hexahydrate, 0.4g samarium chloride hexahydrate, 5.1g ferric chloride hexahydrate and 3.1g ferrous sulfate heptahydrate in a mixed solvent consisting of 80g deionized water and 25g anhydrous ethanol. Stir for 30min under nitrogen protection and sonicate for 20min. Add a mixture containing 10g sodium hydroxide, 1.5g anhydrous sodium carbonate and 120g deionized water dropwise at 4℃. After the addition is complete, mature under nitrogen protection for 2h to obtain the precursor.
[0034] A2: The precursor was vacuum filtered to obtain precipitate A; washed with 200g of deionized water until neutral, transferred to a reaction vessel, 5g of 0.1mol / L trisodium citrate aqueous solution was added, and deionized water was added to 80% of the vessel volume. The pH was adjusted to 9.5 with 1.0mol / L NaOH, and hydrothermally crystallized at 178℃ for 24h; after natural cooling and centrifugation, precipitate B was obtained; washed alternately with 100g of deionized water and anhydrous ethanol, and vacuum dried at 58℃ to obtain nanocrystalline nuclei.
[0035] A3: 5.0 g of nanocrystalline nuclei were ultrasonically dispersed in 30 g of deionized water and 120 g of anhydrous ethanol. 1.4 g of hexadecyltrimethylammonium bromide and 1.8 g of tetraethyl orthosilicate were added. The pH was adjusted to 9.0 with ammonia water, and the mixture was stirred at 38 °C for 8 h. Product A was obtained by magnetic separation. After drying, the product A was dispersed in 150 g of anhydrous ethanol containing 5 g of ammonium nitrate and extracted by stirring at 58 °C for 2 h. Product B was obtained by magnetic separation. Product B was calcined at 400 °C for 2 h in a tube furnace under a nitrogen atmosphere and then cooled. The calcined product was treated in deionized water at 80 °C for 30 min, centrifuged, washed with deionized water to pH 6.5, and vacuum dried at 98 °C to obtain mesoporous silica shell composite microspheres.
[0036] A4: Disperse 3.0g of the composite microspheres in 85g of anhydrous toluene, add 0.7g of 3-mercaptopropyltrimethoxysilane and 0.3g of 3-aminopropyltriethoxysilane, reflux at 108℃ for 12h under nitrogen protection; separate magnetically, wash 3 times each with anhydrous toluene and anhydrous ethanol, and dry under vacuum at 60℃ to obtain the final product. Example
[0037] The difference between this embodiment and Embodiment 1 is that this embodiment provides a process for the resource utilization and treatment of titanium dioxide waste acid, including the following steps: S1: Take 105g of titanium dioxide waste acid, and after sedimentation and coarse filtration, pump it into the reaction tank. Add 0.5g of calcium sulfate dihydrate in advance, stir at room temperature, add a suspension containing 25g of calcium oxide and 225g of deionized water, adjust the pH to 3.5, stir continuously for 30min, let it stand for 2h to obtain the supernatant and the lower precipitate; filter the lower precipitate to dehydrate and obtain the filter mother liquor.
[0038] S2: Pump the supernatant obtained in step S1 into an adsorption tower filled with 8g of thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres. Apply an electromagnetic field (frequency 60Hz, intensity 20mT) to the outer wall of the adsorption tower, collect the adsorbed wastewater, and obtain the adsorbed saturated material in the adsorption tower.
[0039] S3: Discharge the saturated adsorption material into a magnetic separation tank. Place a 0.3T permanent magnet at the bottom of the magnetic separation tank to obtain the separated supernatant and the magnetically enriched material. Return the separated supernatant to the reaction tank in step S1. Wash the magnetically enriched material with 30g of deionized water, transfer it to a regeneration reaction tank, add 25g of dilute hydrochloric acid solution with pH=2.5, stir for 30min, and separate it again through a magnetic field to obtain the regenerated microspheres and desorption regeneration liquid. Wash the regenerated microspheres with 15g of deionized water, dry them under vacuum at 62℃, and then recycle them.
[0040] S4: Combine the desorption regeneration solution obtained in step S3 with the filter press mother liquor obtained in step S1 and pump them into an oxidation reaction tank. Adjust the pH to 4, add 1.0 g of hydrogen peroxide (30 wt%), and introduce air (1.0 m³ / (m²·min)) to obtain the oxidized feed solution. Pump the oxidized feed solution into a primary sedimentation tank, adjust the pH to 5.0 with 10 wt% lime slurry, let it stand for 1 hour to separate the precipitate and the supernatant. Transfer the supernatant to a secondary sedimentation tank. In the sedimentation tank, the pH was adjusted to 8.5 with 10wt% lime milk, stirred continuously for 45 minutes, and allowed to settle for 2 hours to separate the supernatant and the precipitate. The supernatant was discharged. The precipitate was filtered and dried at 120℃ to obtain calcium sulfate dihydrate. The adsorbed wastewater obtained in step S2 was pumped into the neutralization tank, 10wt% lime milk was added to adjust the pH to 8.5, and allowed to settle. The supernatant was discharged after meeting the standards. The bottom sludge was filtered and combined with the precipitate from step S1 for disposal.
[0041] Preparation of thiol- and amino-bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres: A1: Dissolve 1.2g cerium chloride hexahydrate, 0.6g samarium chloride hexahydrate, 5.5g ferric chloride hexahydrate and 3.4g ferrous sulfate heptahydrate in a mixed solvent consisting of 100g deionized water and 30g anhydrous ethanol. Stir for 30min under nitrogen protection and ultrasonically disperse for 40min. Add a mixture containing 12g sodium hydroxide, 2.0g anhydrous sodium carbonate and 140g deionized water dropwise at 6℃. After the addition is complete, mature under nitrogen protection for 2h to obtain the precursor.
[0042] A2: The precursor was vacuum filtered to obtain precipitate A; washed with 300g of deionized water until neutral, transferred to a reaction vessel, 10g of 0.1mol / L trisodium citrate aqueous solution was added, and deionized water was added to 80% of the vessel volume. The pH was adjusted to 10.0 with 1.0mol / L NaOH, and hydrothermally crystallized at 182℃ for 30h; after natural cooling and centrifugation, precipitate B was obtained; washed alternately with 150g of deionized water and anhydrous ethanol, and vacuum dried at 62℃ to obtain nanocrystalline nuclei.
[0043] A3: 5.0 g of nanocrystalline nuclei were ultrasonically dispersed in 40 g of deionized water and 140 g of anhydrous ethanol. 1.6 g of hexadecyltrimethylammonium bromide and 2.2 g of tetraethyl orthosilicate were added. The pH was adjusted to 9.5 with ammonia water, and the mixture was stirred at 42 °C for 8 h. Product A was obtained by magnetic separation. After drying, the product A was dispersed in 200 g of anhydrous ethanol containing 8 g of ammonium nitrate and extracted by stirring at 62 °C for 2 h. Product B was obtained by magnetic separation. Product B was calcined at 450 °C for 4 h in a tube furnace under a nitrogen atmosphere and then cooled. The calcined product was treated in deionized water at 90 °C for 60 min, centrifuged, washed with deionized water until pH=7.0, and vacuum dried at 102 °C to obtain mesoporous silica shell composite microspheres.
[0044] A4: Disperse 3.0g of the composite microspheres in 95g of anhydrous toluene, add 0.9g of 3-mercaptopropyltrimethoxysilane and 0.5g of 3-aminopropyltriethoxysilane, reflux at 112℃ for 14h under nitrogen protection; separate magnetically, wash 3 times each with anhydrous toluene and anhydrous ethanol, and dry under vacuum at 80℃ to obtain the final product.
[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that, in the preparation of thiol- and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres, cerium chloride hexahydrate and samarium chloride hexahydrate are not added in step A1, while the other reagents and operations are exactly the same.
[0046] Comparative Example 2 The difference between this comparative example and Example 1 is that, in preparing thiol- and amino-functionalized cerium samarium co-doped ferrite-silica composite porous microspheres, 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane are not added in step A4, while the rest of the operations are exactly the same.
[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that, in preparing the thiol- and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres, step A3 is skipped, and the nanocrystal nuclei obtained in step A2 are directly used for grafting in step A4. The rest of the operations are exactly the same.
[0048] In accordance with national and industry standard testing specifications, a series of standardized tests were conducted on the titanium dioxide waste acid resource utilization treatment processes described in Examples 1-3 and Comparative Examples 1-3.
[0049] Take 6.5g each of the thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres prepared in Examples 1-3 and Comparative Examples 1-3 (the comparative examples were prepared according to their respective distinguishing characteristics), and fill them into magnetically stabilized fluidized bed adsorption towers of the same specifications (height-to-diameter ratio 5:1, filling volume 65%). Under the same operating conditions (supernatant source is the same batch of supernatant obtained in step S1 of Example 1, waste acid treatment amount 100g, space velocity 2.0 BV / h, magnetic field frequency 55Hz, intensity 15mT, running time 10h), the adsorption performance is tested.
[0050] Fe 2+ Adsorption capacity determination: Initial supernatant and post-adsorption effluent were collected, and absorbance was measured at 510 nm using the o-phenanthroline spectrophotometric method. Fe was calculated based on the standard curve. 2+ Concentration and adsorption capacity are expressed by the formula q = (C0 - C2) / (C2) e The calculation is based on C0 × V / m, where C0 is the initial concentration (mg / L), and C... eV represents the concentration after adsorption (mg / L), V represents the volume of waste acid treated (0.1L), and m represents the mass of the microspheres (0.0065kg).
[0051] SO4 2- Adsorption capacity determination: Take the initial supernatant and the effluent after adsorption, and use the gravimetric method to add excess BaCl2 solution to generate BaSO4 precipitate. After ignition and weighing, calculate the SO4 content. 2- The concentration is then used to calculate the adsorption capacity using the same formula.
[0052] Determination of total iron concentration in effluent: Take the effluent after adsorption and use hydroxylamine hydrochloride to remove Fe. 3+ Reduced to Fe 2+ Then add o-phenanthroline for color development, measure the absorbance at 510 nm, and calculate the total iron concentration (mg / L) according to the standard curve.
[0053] effluent SO4 2- Concentration determination: Take the effluent after adsorption, add BaCl2 solution, and determine the turbidity using spectrophotometry. Calculate SO4 based on the standard curve. 2- Concentration (mg / L).
[0054] Magnetic separation time determination: 1g of each microsphere was dispersed in 50mL of deionized water, and the time (s) required from the start of magnetic field application to the complete clarification of the supernatant and the complete adsorption of the solid to the container wall was recorded under a 0.25T permanent magnet magnetic field.
[0055] After 10 cycles, Fe 2+ Adsorption capacity retention rate determination: The microspheres of Examples 1-3 and Comparative Examples 1-2 were regenerated according to the step of claim S3 (elution with dilute hydrochloric acid at pH=2.3, vacuum drying at 60℃). The adsorption-regeneration operation was repeated 10 times. The Fe²⁺ adsorption capacity after the 10th adsorption was recorded. The retention rate (%) was calculated as (10th adsorption capacity / 1st adsorption capacity) × 100%.
[0056] The performance test data above are shown in Table 1.
[0057] Table 1 Performance Test Results <![CDATA[Fe 2+ Adsorption capacity (mg / g) 58.3 55.2 61.5 56.8 17.6 18.2 <![CDATA[SO4 2- Adsorption capacity (mg / g) 126.5 118.4 134.2 51.2 108.6 38.7 Total iron concentration in effluent (mg / L) 12.5 18.3 8.6 15.2 186.5 172.4 <![CDATA[Effluent SO4 2- Concentration (mg / L)]]> 215 268 182 612 348 698 Magnetic separation time (s) 25 28 22 26 24 Inseparable <![CDATA[Fe after 10 cycles 2+ Adsorption capacity retention rate (%)]]> 83.5 80.2 85.1 72.3 78.5 - As can be seen from the above, Examples 1-3 clearly solve several key technical problems existing in the resource utilization process of titanium dioxide waste acid in the prior art compared with Comparative Examples 1-3.
[0058] Comparative Example 1, lacking the addition of cerium and samarium rare earth elements, had lower SO4 content. 2- The adsorption capacity is only 51.2 mg / g, and the effluent SO4 content is low. 2-The concentration was as high as 612 mg / L, which is much higher than the 118.4-134.2 mg / g and 182-268 mg / L of Examples 1-3, indicating that cerium-samarium co-doping significantly enhances the material's coordination and capture ability for sulfate ions by forming surface sulfate complexes, thus solving the problem of low anion removal efficiency of existing adsorbent materials under strongly acidic conditions.
[0059] Comparative Example 2, due to the lack of both thiol and amino groups for bifunctionalization, exhibits Fe... 2+ The adsorption capacity was only 17.6 mg / g, while the total iron concentration in the effluent was as high as 186.5 mg / L, whereas the Fe in Examples 1-3... 2+ The adsorption capacity reached 55.2-61.5 mg / g, while the total iron concentration in the effluent was only 8.6-18.3 mg / L, proving that the thiol group effectively adsorbs Fe. 2+ Coordination complexation and amino protonation electrostatic attraction are key to the efficient removal of heavy metals, solving the problems of poor selectivity and inability to synergistically remove cations and anions by traditional materials.
[0060] Comparative Example 3, due to the lack of a mesoporous silica shell, Fe 2+ The adsorption capacity was only 18.2 mg / g, while the magnetic separation time of Examples 1-3 was only 22-28 s, and the adsorption capacity retention rate was still 80.2-85.1% after 10 cycles. This indicates that the silica shell effectively protected the internal magnetic core from acid corrosion, while providing silanol groups for capturing Al. 3+ This solves the core defects of existing magnetic adsorption materials, such as easy dissolution and deactivation in strong acid environments and inability to be recycled.
[0061] In summary, Examples 1-3, through a triple synergistic design of cerium-samarium co-doping, bifunctional group grafting, and mesoporous shell coating, simultaneously achieved Fe... 2+ Al 3+ and SO4 2- The efficient removal, rapid magnetic separation and recovery, and excellent cycle stability of the material transform valuable metals and sulfate ions in titanium dioxide waste acid into recyclable resources, completely overcoming the performance shortcomings of the single-component material represented by the comparative example.
Claims
1. A process for the resource utilization and treatment of waste acid from titanium dioxide production, characterized in that, Includes the following steps: S1. By weight, coarsely filter 95-105 parts of titanium dioxide waste acid, add 0.1-0.5 parts of calcium sulfate dihydrate beforehand, stir, add a suspension containing 15-25 parts of calcium oxide and 135-225 parts of deionized water, adjust the pH to 3.2-3.5, stir, and let it stand to settle to obtain the supernatant and the lower precipitate; dehydrate the lower precipitate by pressure filtration to obtain the mother liquor. S2. Pump the supernatant obtained in step S1 into an adsorption tower filled with 5-8 parts of mercapto and amino bifunctional cerium samarium co-doped ferrite-silica composite porous microspheres. Apply an electromagnetic field to the outer wall of the adsorption tower, collect the adsorbed wastewater, and obtain the adsorbed saturated material in the adsorption tower. S3. Magnetically separate the adsorbed saturated material to obtain the separated supernatant and the magnetically enriched material; return the separated supernatant to the reaction vessel of step S1; wash the magnetically enriched material, add dilute hydrochloric acid solution, stir, and separate to obtain the regenerated mercapto- and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres and desorption regeneration solution; wash the regenerated mercapto- and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres with deionized water, vacuum dry, and then recycle them; S4. Combine the desorption regeneration solution obtained in step S3 with the filter press mother liquor obtained in step S1, adjust the pH to 3-4, add hydrogen peroxide to obtain the oxidized feed solution; adjust the pH of the oxidized feed solution to 4.0-5.0, separate, and obtain the precipitate and the supernatant after separation. Adjust the pH of the separated supernatant to 7.5-8.5, stir, and separate to obtain an upper supernatant and a lower precipitate; discharge the upper supernatant; filter the lower precipitate by pressure and dry it; pump the adsorbed wastewater obtained in step S2 into a neutralization tank, add lime slurry to adjust the pH to 6-9, and let it stand to settle.
2. The titanium dioxide waste acid resource utilization and treatment process according to claim 1, characterized in that, In step S1, the settling time is 1-2 hours.
3. The titanium dioxide waste acid resource utilization and treatment process according to claim 1, characterized in that, In step S2, the filling volume of the thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres is 60-70% of the effective volume of the adsorption tower.
4. The titanium dioxide waste acid resource utilization and treatment process according to claim 1, characterized in that, In step S3, the magnetic field strength of the permanent magnet is 0.2-0.3T.
5. The titanium dioxide waste acid resource utilization and treatment process according to claim 1, characterized in that, In step S4, the drying temperature is 105-120℃.
6. The titanium dioxide waste acid resource utilization and treatment process according to any one of claims 1-5, characterized in that, The preparation steps of the thiol and amino bifunctionalized cerium samarium co-doped ferrite-silica composite porous microspheres include: A1. By weight, dissolve 0.8-1.2 parts of cerium chloride hexahydrate, 0.4-0.6 parts of samarium chloride hexahydrate, 5.1-5.5 parts of ferric chloride hexahydrate, and 3.1-3.4 parts of ferrous sulfate heptahydrate in a mixed solvent consisting of 80-100 parts of deionized water and 25-30 parts of anhydrous ethanol. Under nitrogen protection, stir and ultrasonically disperse. At 4-6℃, add dropwise a mixed solution containing 10-12 parts of sodium hydroxide, 1.5-2.0 parts of anhydrous sodium carbonate, and 120-140 parts of deionized water. After the addition is complete, ripen under nitrogen protection to obtain the precursor. A2. Vacuum filter the precursor to obtain precipitate A; wash precipitate A with deionized water, transfer it to a reaction vessel, add 5-10 parts of trisodium citrate aqueous solution, replenish with deionized water, adjust the pH to 9.5-10.0, and hydrothermally crystallize at 178-182℃; after the reaction is complete, allow it to cool naturally, centrifuge to obtain precipitate B; wash precipitate B with deionized water and anhydrous ethanol, and vacuum dry at 58-62℃ to obtain nanocrystalline nuclei; A3. 5.0 parts of nanocrystalline nuclei were ultrasonically dispersed in a mixed solvent consisting of 30-40 parts of deionized water and 120-140 parts of anhydrous ethanol. 1.4-1.6 parts of hexadecyltrimethylammonium bromide and 1.8-2.2 parts of tetraethyl orthosilicate were added, and the pH was adjusted to 9.0-9.
5. The mixture was stirred at 38-42℃. Magnetic separation was performed to obtain product A. After drying, product A was dispersed in 150-200 parts of anhydrous ethanol solution containing 5-8 parts of ammonium nitrate. Extraction was performed with stirring at 58-62℃, followed by magnetic separation to obtain product B. Product B was placed in a tube furnace and calcined at 400-450℃ under a nitrogen atmosphere. After cooling, the calcined product was obtained. The calcined product was placed in deionized water and treated at 80-90℃. After centrifugation, solid A was obtained. Solid A was washed with deionized water and vacuum dried at 98-102℃ to obtain composite microspheres with a mesoporous silica shell. A4. Disperse 3.0 parts of composite microspheres with mesoporous silica shells in 85-95 parts of anhydrous toluene, add 0.7-0.9 parts of 3-mercaptopropyltrimethoxysilane and 0.3-0.5 parts of 3-aminopropyltriethoxysilane and mix. Under nitrogen protection, reflux at 108-112℃. After the reaction is completed, magnetic separation is performed to obtain solid B. Wash solid B with anhydrous toluene and anhydrous ethanol and dry it under vacuum at 60-80℃.
7. The titanium dioxide waste acid resource utilization and treatment process according to claim 6, characterized in that, In step A1, the ultrasonic dispersion time is 20-40 minutes.
8. The titanium dioxide waste acid resource utilization and treatment process according to claim 6, characterized in that, In step A2, the hydrothermal crystallization time at 178-182℃ is 24-30 hours.
9. The titanium dioxide waste acid resource utilization and treatment process according to claim 6, characterized in that, In step A3, the calcination time at 400-450℃ is 2-4 hours.
10. The titanium dioxide waste acid resource utilization and treatment process according to claim 6, characterized in that, In step A4, the reflux reaction is carried out at 108-112℃ for 12-14 hours.
